Objective post-concussion sleep quality: exploring the effects of concussion and determining its relationship with recovery outcomes in children and adolescents - Fisher, Michael (My University, 2020)
Background: Sleep is commonly disrupted following pediatric concussion. Recently, post-concussion sleep quality has been identified as a potential factor that may influence recovery length. However, few studies have examined this relationship using objective sleep measures in a pediatric population. Nor, have any studies examined the trajectory of objective sleep parameters after pediatric concussion. Objectives: The purpose of this thesis is to: 1) Provide a review of current literature regarding pediatric concussion, healthy sleep quality, and sleep quality in the context of concussion and recovery from concussion; 2) Examine how objective sleep outcomes are affected and change post-concussion in children and adolescents; 3). Explore how post-concussion sleep quality parameters are related to length of recovery, quality of life (QOL), and depression symptomatology; and 4) Discusses the results from the two studies in the context of current literature and of each other. Methods: Sleep quality was inferred from the outcomes of five objective sleep parameters. Sleep parameters were measured using actigraphy in children and adolescents with concussion following return to school (RTA) and return to activity (RTA) protocols. Sleep data during the initial 4 weeks of recovery was assessed as an outcome, as a predictor of recovery length, and as a correlate of quality of life (QOL) and depression symptomatology Results: Most objective post-concussion sleep quality parameters were adversely affected by concussion but show trajectories indicating improvement throughout the initial 4 weeks of recovery. Sleep quality parameters were not associated with time to complete return to school or activity protocols. Sleep parameters were not strongly correlated with QOL or depression symptomatology outcomes. Conclusions: These results indicate that objective post-concussion sleep quality is impaired following concussion, but these outcomes do not appear to be associated with recovery, QOL or depression symptomatology. Other factors, or improvements in sleep quality may better explain recovery outcomes.
Analysis of post-concussion sleep quality in youth
Keywords: concussion; sleep quality; actigraphy; pediatric; recovery